Cities in globalization - Cabigon, Josefina V., 1946-2011 (2006)
This paper highlights two evidence-based views in understanding the nature of cities in globalization. The first view is that cities are forming a world city network with a particular geography that is city-centered (command power remaining in core-located cities and network power in non-core cities) to impinge on future social change. This world city network is a part of a globalization processes that are inevitable and irreversible. It is conceptualize as an interlocking network with cities as a nodes in spaces of flows linking localities in the whole network. It constitutes the knowledge constellation for the production of services, and agencies, such as business firms, as the sub-nodal level at creates and provides the services as the prime agency of network production and reproduction. US cities are command power centers but are always most strongly connected to other cities within the US (dominance of space of places) and less prominent in the world city network (prominence of space of flows) - a pattern of emerging freedom of cities, especially in weak states. The world city network is not inherently regressive in nature; it can service global capital as well as create a new economical policies (concern for networks of trade and finance) operating through the principles of cooperation and mutuality. The second view is that cities are now reflecting a clear culture-economy overlap, with global cities such as New York, London, Paris and Tokyo emerging as centers of the global economy and cultural industries and are also the prominent destinations of immigrants who tend to be vulnerable to exploitation and to congregate in enclaves. Major cities in the US are reflecting a city growth coalition of profit seekers, political leaders, and cultural institutions resulting in the economic becoming cultural and cultural becoming economic. Marketing the city's cultural offerings aim for both consumption of culture and generation of income in the city. With world cities in globalization operating as a world city network, studying cities in terms of relations between and among cities, and the link between cities as a process is necessary. Research gaps such as lack of data and of studies of relations between cities as state-centric are realities. Specifically, demographers who are more known for providing populations with news expressed meaningfully in terms of numbers and rates face the problem of data that reflect relations on migration between and among network.
Keywords: Globalization -- Social aspects; Cities and towns; Capitals (Cities) -- Globalization